Comparative study for removal of nitro-heterocyclic explosives using magnetic graphene nanocomposites. Issue 8 (2nd August 2020) - Khurana, Ishani; Shaw, Ajay Kumar; , Bharti; Khurana, Jitender M.; Rai, Pramod Kumar
Abstract: In this manuscript, RDX (Royal Demolition eXplosive) and HMX (High Melting eXplosive) were removed from water that is mainly polluted by military activities. Two different forms of magnetic graphene oxide nanocomposites, α-Fe2 O3 -rGO (hematite-reduced graphene oxide) and nZVI-rGO (nano zero valent iron-reduced graphene oxide) have been evaluated for decontamination of water containing these carcinogenic explosives. Comparative adsorption studies were carried out considering contact time, pH and adsorbent dosage for all the adsorbent–adsorbate systems. Batch adsorption experiments at varied concentrations of RDX and HMX were conducted. The experimental results better fit in pseudo second order model following Freundlich isotherm. Magnetic nature of both adsorbents is suitable for their easy separation from contaminated water in presence of an external magnetic field. α-Fe2 O3 -rGO showed higher adsorption capacities for HMX and RDX, this was supported by the physio-chemical properties of the adsorbent. Therefore, it could be potentially upscaled and used commercially for purification of water containing explosives.